Remarkable electrically actuation performance in advanced acrylic-based dielectric elastomers without pre-strain at very low driving electric field. (14th February 2018) - Zhao, Yu; Zha, Jun-Wei; Yin, Li-Juan; Gao, Zhan-Sheng; Wen, Yong-Qiang; Dang, Zhi-Min
Abstract: Most dielectric elastomers (DEs) need high operating electric field (>100 kV/mm) and the essential pre-strains to achieve satisfied actuation, which limits their widespread application. In this work, we prepare a series of high performance DEs using the common acrylate monomers through a versatile method. By adjusting the component of polymers, the advanced DE possess a high actuation coefficient β (51.54 MPa −1 ) and shows a high actuated strain of 52.08% at a low electric field of 21.57 kV/mm without pre-strain. It is also found that the actuated strain of the c-p (BA-GMA)-3 is almost 4.2 times higher than that of VHB 4910. Furthermore, the advanced DE material is used to fabricate into a bend actuator, which can bend a angel of 180° and show a good electromechanical response. The present work opens a new strategy for designing advanced dielectric elastomers displaying high actuated strain without pre-strain at very low electric field. Graphical abstract: Image 1 Highlights: Series of acrylic-based dielectric elastomers are successfully prepared to fabricated DEAs through a simple method. The advanced dielectric elastomers can display high actuated strain at a very low driving electric field without pre-strain. The elastomer film can be fabricated into a bend actuator which can drastically bend.